2019
DOI: 10.1177/0047287519843188
|View full text |Cite
|
Sign up to set email alerts
|

Customer Resistance to Tourism Innovations: Entrepreneurs’ Understanding and Management Strategies

Abstract: Customer resistance is the greatest risk to innovation for the entrepreneur. The aim of this exploratory study is to provide insights into this underdeveloped area in the tourism innovation literature. A qualitative approach is adopted to understand the resistance experienced by 57 entrepreneurs when introducing their innovations into the market, the causes and the actions taken to minimize resistance. Findings indicate that most entrepreneurs often encounter resistance from sceptical customers, satisfied with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 69 publications
2
12
0
2
Order By: Relevance
“…Figure 1 illustrates this growing trend in audio-visual patterns in tourism and is in line with researchers' assertion that the development of internet and digital tools has created several possibilities for innovations in tourism (Wang et al, 2016). The study, however, is one of the few ones to explore innovation in tourism via longitudinal data, facilitating a better understanding of the dynamic and complex innovation process (Rodriguez-Sanchez et al, 2020;Williams et al, in press).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Figure 1 illustrates this growing trend in audio-visual patterns in tourism and is in line with researchers' assertion that the development of internet and digital tools has created several possibilities for innovations in tourism (Wang et al, 2016). The study, however, is one of the few ones to explore innovation in tourism via longitudinal data, facilitating a better understanding of the dynamic and complex innovation process (Rodriguez-Sanchez et al, 2020;Williams et al, in press).…”
Section: Resultssupporting
confidence: 75%
“…From Table 2 it becomes evident that tourism audio-visual patents registered have the second highest rate of growth after micro-structural and nano-technology, and they surpass well-known innovative sectors like food chemistry and telecommunications, further validating the classification of tourism as an innovation-oriented sector. This finding is surprising considering the recognised lack of empirical research documenting innovation in tourism (Rodriguez-Sanchez et al, 2020;Williams et al, in press;Singh et al, 2020;Valenca et al, 2020). 2 Here] The next step involved performing content analysis of the identified 4,237 patents' abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…Xu, Hao, and Han argued that information search has become an important part of the behavior of Net Generation consumers who communicate easily with other people by taking advantage of the characteristics of Internet communities [67]. Sánchez, Williams, and García-Andreu suggested that communication strategies are essential to reduce risks and build trust [86]. However, information search in different stages has a varying influence on action.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Innovation begins when entrepreneurs sense a new opportunity. This discovery task can be a source of uncertainty especially if the gap identified is not closely aligned with the customers’ needs (Rodriguez, Williams, and Andreu 2019). After the discovery, the innovative idea is repeatedly evaluated through engaging with informed individuals, undertaking preliminary market testing or financial viability analysis (Rodriguez, Williams, and Brotons 2017).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…The innovation process culminates with the commercialization or adoption of the innovation, the moment of truth when the assessment of risks and uncertainties is ultimately tested. Most innovations fail because of limited market understanding and failure to overcome customers’ resistance (Kleijnen, Lee, and Wetzels 2009; Heidenreich and Kraemer 2015; Rodriguez, Williams, and Andreu 2019), probably the most persistent of uncertainties, although the appearance of unanticipated competitors and poorly timed market entry are also important. Technological issues also emerge either because it is inadequate (poorly managed risk), or is undermined by unforeseen competing technologies (uncertainty).…”
Section: Theoretical Reviewmentioning
confidence: 99%